Optimization of Crude Oil Transmission Process by Installing Electric Heat Tracing in Off-Plot Piping - Oksil Venriza; Cut Reza Wahyuni (Scientific Contributions Oil and Gas, 2024)
Crude oil transmission is distributing crude oil from one plane to another. Problems that often occur in the crude oil transmission process are freezing or crystallization of paraffin when the temperature in the environment reaches the Pour Point Temperature. Usually, this can be overcome by injecting Pour Point Depressant into crude oil. However, using Pour Point Depressant is still ineffective if used continuously. This is because Pour Point Depressant can affect the quality of crude oil and increase environmental risks and if the transmission process is carried out on a large scale, it will also require large costs to meet these needs. Therefore, this research examined the application of constant wattage type Electric Heat Tracing as an alternative to Pour Point Depressant in the off-plot piping section, precisely in the PT ABC transmission pipe network. By carrying out transient simulations using OLGA version 2022.1.1 software, several scenarios for the most optimal Electric Teat Tracing installation in the crude oil transmission process were developed while minimizing the costs incurred. From the simulations carried out, it is known that the constant wattage type Electric Teat Tracing with a capacity of 3 x 100 kW can maintain the pipe temperature above the Pour Point Temperature value, namely 111ÂºF with 2 installation spots KP 1+700 to KP 3+200 and KP 5+800 to KP 7 +300. Apart from that, the use of Electric Heat Tracing is also more economical compared to Pour Point Depressant injection.